Reassessing the Influence of STP Strategic Choices on Sales Performance: Evidence from a Food and Beverage SME - Nurhayani; Sutrisno; Ilham Abu (Global Research Collaboration, 2025)
This study investigates the extent to which strategic decisions in segmentation, targeting, and positioning (STP) translate into short-term sales performance within a food-and-beverage small enterprise. Using a descriptive–quantitative approach, the research employed a within-firm sampling frame covering all 36 employees and collected data through standardized survey instruments. Prior to hypothesis testing, the measurement model was evaluated to ensure construct validity and internal reliability. Multiple linear regression was then applied to estimate both the individual and combined effects of the three STP dimensions on sales outcomes, supported by conventional diagnostic checks for statistical assumptions. The empirical results reveal that while segmentation, targeting, and positioning yield positive coefficient directions, none attain statistical significance, and their joint contribution adds only marginal explanatory power. These findings imply that STP strategies, when implemented in isolation, may not directly enhance sales performance in the short run. The effectiveness of STP appears contingent on complementary managerial actions such as product/menu refinement, pricing adaptability, promotional intensity, service innovation, and localized market engagement. From a managerial standpoint, the study underscores the importance of aligning strategic marketing determinations with operational execution rather than relying solely on strategic intent. Theoretically, the research adds micro-level evidence to the mixed debate regarding the STP–performance linkage in small service firms. Future studies are encouraged to incorporate consumer-side metrics, experimental designs, or transaction-level panel data to better capture how STP strategies generate value throughout the customer decision process.